(untitled) (Eurasian Medical Research Periodical, 2022)
The article provides data on the result of a molecular genetic study of the genotypic characteristics of Helicobacter pylori in the formation of NSAIDs of gastropathy in patients with rheumatoid arthritis. Purpose of the study. Molecular-genetic study of the genotypic features of H. pylori in the formation of NSAID gastropathy in RA patients for the prevention of gastroduodenal lesions. Materials and research methods. The research is based on the genomic DNA of H. pylori., isolated from a biopsy of the antrum of 82 patients with RA and 22 healthy individuals. The genotype of H. pylori CagA, vacam1, vacam2, vacAs1, vacas2, vacas1b, vacas1c, icea1, icea2, HP was determined in biopsy samples. Results. Thus, according to the molecular genetic study, the pathogenic strain VacA m2 (х2=4,12 р=0.011), IceA 2 (=6,71 р=0.036) prevails in patients with RA of the 2nd degree of activity. Conclusion. Our preliminary results suggest that the H. Pylori vaca m2 and icea 2 may be considered as additional markers of NSAID-gastropathy in rheumatoid arthritis.